"Mein Trost, Kampf und Sieg ist Christus": Martin Luthers eschatologische Theologie nach seinen Reihenpredigten über 1. Kor 15 (1532/33) - Wiemer, Axel (Theologische Bibliothek Töpelmann, 2003)
The work presents a comprehensive systematic account of Luther's eschatological theology on the basis of the 17 sermons which he preached on 1 Corinthians 15 in 1532 and 1533. The interpretation of the sermons provides exemplary evidence for the thesis that Luther's theology is totally based on the promise of full completion. This applies both to his basic decisions in the doctrine of faith and the word and of the language of faith. It applies equally to the doctrine of the Resurrection, which covers the whole span from creation and the fall through salvation to the consummation of Christ's victory in "the death of death", and to Luther's discourse on life in this world.